Housing inequality in the United States: a decomposition analysis of racial and ethnic disparities in homeownership - Sanjaya DeSilva; Yuval Elmelech (Levy Economics Institute of Bard College, 2009)
In recent years, as the homeownership rate in the United States reached its highest level in history, homeownership itself remained unevenly distributed, particularly along racial and ethnic lines. By using data from the 2000 Integrated Public Use Microdata Series (IPUMS) and 2006 American Community Survey (ACS) to study the trajectory into homeownership of black, Asian, white, and Latino households, this paper explores the various socioeconomic and demographic characteristics, as well as the distinct immigration experiences and spatial patterns that shape racial and ethnic inequality in homeownership. The unique (merged) dataset enables the authors to distinguish assimilation (length of residence) from immigration cohort effects, and to control for various spatial characteristics at the PUMA (Public Use Microdata Area) level. The paper employs a decomposition technique that delineates the distinct effects that composition differentials have on the visible white-minority disparity in homeownership. The findings reveal substantial differences along racial-ethnic lines, highlight the importance of immigration and spatial context in determining Asian and Mexican homeownership rates, and emphasize the unique role that family structure and unobserved factors (e.g. prejudice and discrimination) continue to play in shaping the black-white homeownership gap.
Keywords: J15; R21; R23; 330; Homeownership; race; ethnicity; immigration